A comparative study to assess the independency of lipid profile and blood sugar levels as a diagnostic marker in oral cancer and precancerous disorders - Rohan Sachdev; Kriti Garg; Garima Singh; Vishal Mehrotra (Wolters Kluwer Medknow Publications, 2020)
Context: Lipids are the main cell membrane components important for different biological functions including cell growth and division of normal and malignant tissues. Low lipid values in cancer, precancer lesion, and condition may be due to of lipid peroxidation and also lipids play a key role in the higher utilization of lipids including total cholesterol (TC) and triglycerides (TG) for new membrane biogenesis. Aims: The present study was aimed to assess the independency and comparison of serum lipid profile and blood glucose level in patients with oral carcinoma and precancerous lesions and conditions. Settings and Design: The total sample sizes of 180 individuals were chosen in a 2-year duration: 60 were diagnosed with leukoplakia/oral submucous fibrosis, 60 with oral carcinoma, and 60 of the control group. Subjects and Methods: The serum triglycerides (TGs) were estimated by GPO-PAP End Point Assay method, total cholesterol (TC) by CHOD-PAP, and high-density lipoprotein (HDL) cholesterol by PEG-CHOD-PAP End Point Assay method with lipid clearing factors. The low-density lipoprotein (LDL) and very LDL (VLDL) levels were calculated using Friedewald's equation. Statistical Analysis Used: Collected data were statistically calculated by Student's t-test and by Chi-square test with SPSS version 17. All values were considered statistically significant for a value of P < 0.05. Results: This study showed that parameters TC, TG, and HDL of lipid profile were reduced in the oral precancerous study group as compared to the oral carcinoma study group, whereas in all the study groups, no statistically changes were found in LDL, VLDL, fasting blood sugar, and postprandial blood sugar levels. Conclusions: Low serum value of TC, TG, and HDL may be the indicator for the increased risk of developing precancer diseases and oral cancer in healthy individuals with tobacco habits. Low lipid profile parameters can be used as diagnostic markers in assessment of oral cancer and precancer along with other parameters of biochemical markers.